What drives students’ investment interest in the sharia capital market? - Femas Khairul Ikhfani; Fauzan Fuadi; Fitria Fertha Agustina; Andi Mulyono (Journal of Accounting and Digital Finance, 2025)
This study examines the effects of Sharia financial literacy, minimum capital, social media influencers, and technological advancement on university students’ investment interest in the Sharia capital market in Lampung Province. Using a quantitative approach, primary data were collected through an online questionnaire administered to 100 students from various universities in Lampung Province. The data were analyzed using multiple linear regression. The results show that Sharia financial literacy has a significant effect on students’ investment interest, indicating that greater understanding of Sharia principles and financial instruments increases students’ willingness to invest. Social media influencers also have a significant effect, suggesting that information exposure and persuasion from digital figures help shape investment interest. In contrast, minimum capital and technological advancement do not have a significant effect on students’ investment interest in the Sharia capital market. Overall, these findings highlight the importance of strengthening Sharia financial literacy and leveraging social media–based education to encourage greater student participation in the Sharia capital market.